Spatial data starter kit for OnSSET energy planning in Kitui County, Kenya - Mwendwa, DM; Tchouambe, J; Hu, E; Lanza, MF; Brener, AB; Hwang, G; Khanfar, L; Leonard, A; Hirmer, S; McCulloch, M (Elsevier, 2022)
The 2019 Energy Act requires each of Kenya’s 47 counties to independently develop energy plans. As county energy planning accelerates, it is important to understand the availability and readiness of data required to facilitate it. This article identifies, evaluates, and pre-processes openly available data to facilitate county-level energy planning using the Open Source Spatial Electrification Tool (OnSSET) in Kitui County, Kenya. In this way, it provides a ready-to-use starter kit of data inputs for county-level OnSSET analysis, and guidance to replicate this work in other counties. We classify the readiness level of each data type for county energy planning on a traffic light scale (i.e. green, amber, red) based on availability, accessibility, recency, accuracy, spatial resolution, and format (i.e. whether processing is required before use). Of the 25 core data inputs for OnSSET at the county-level, we find that 14 have a green, six have an amber, and five have a red readiness-level. Data processing requirements are documented, and the processed data for Kitui county are made available as a ready-to-use set of input parameters for OnSSET. While this data was collected for Kitui, the data sources and processing steps are largely applicable in other counties.